The Guide-based Automatic Creation of Verified Test Scenarious - P. D. Drobintsev; V. P. Kotlyarov; A. A. Letichevsky (Моделирование и анализ информационных систем, 2013)
This paper presents an overview of technology of the automated generation of test scenarios based on guides. The usage of this technology can significantly improve the quality of the developed program products. In order to ground the technology creation, the main problems that occur during the development and testing of the large industrial systems, are described, as well as the methodologies of software verification on conformity to product requirements. The potentialities of tools for automatic and semi-automatic generation of a test suite by using a formal model in UCM notation are demonstrated, as well as tools for verification and automation of testing.